Versatile lysine dendrigrafts and polyethylene glycol hydrogels with inherent biological properties: in vitro cell behavior modulation and in vivo biocompatibility. Issue 6 (18th September 2020) - Carrancá, Mariana; Griveau, Louise; Remoué, Noëlle; Lorion, Chloé; Weiss, Pierre; Orea, Valérie; Sigaudo‐Roussel, Dominique; Faye, Clément; Ferri‐Angulo, Daniel; Debret, Romain; Sohier, Jérôme
Abstract: Poly(ethylene glycol) (PEG) hydrogels have been extensively used as scaffolds for tissue engineering applications, owing to their biocompatibility, chemical versatility, and tunable mechanical properties. However, their bio‐inert properties require them to be associated with additional functional moieties to interact with cells. To circumvent this need, we propose here to reticulate PEG molecules with poly(L‐lysine) dendrigrafts (DGL) to provide intrinsic cell functionalities to PEG‐based hydrogels. The physico‐chemical characteristics of the resulting hydrogels were studied in regard of the concentration of each component. With increasing amounts of DGL, the cross‐linking time and swelling ratio could be decreased, conversely to mechanical properties, which could be tailored from 7.7 ± 0.7 to 90 ± 28.8 kPa. Furthermore, fibroblasts adhesion, viability, and morphology on hydrogels were then assessed. While cell adhesion significantly increased with the concentration of DGL, cell viability was dependant of the ratio of DGL and PEG. Cell morphology and proliferation; however, appeared mainly related to the overall hydrogel rigidity. To allow cell infiltration and cell growth in 3D, the hydrogels were rendered porous. The biocompatibility of resulting hydrogels of different compositions and porosities was evaluated by 3 week subcutaneous implantations in mice. Hydrogels allowed an extensive cellular infiltration with a mild foreign body reaction, histological evidence of hydrogel degradation, and neovascularization.